HUBUNGAN LAMANYA MENJALANI HEMODIALISIS DENGAN DEPRESI PADA KLIEN GAGAL GINJAL KRONIK: Depression in chronic kidney failure - Jundiah, Raden Siti; Dirgahayu, Ingrid; Rahmadina, Fita Nisa (Jurnal Keperawatan 'Aisyiyah, 2019)
Terminal Kidney Failure (GGT) is irreversible kidney damage and is the last stage of kidney disease with a decrease in kidney function<15ml/min[1]. The increased incidence of terminal renal failure [GGT], clients requires to undergo haemodialysis therapy. The responses that appeared in GGT patiens undergoing hemidialysis therapy are physical, psychological, social, and spiritual responses. The psychological impact in clients with GGT who undergoing haemodialysis dan be caused by along course of the diseases [2]. Client of GGT ussualy have to undergo dialysis therapy throughout their life and require 12-15 hours per week, or at least 3-4 hours each time. This therapy must be lived by clients for life. This cause psycholigical problems as depression[3]. The purpose of this study was determine the relationship between the lenght of haemodialysis and depression in chronic renal failure clients in Majalaya District Hospital Bandung. This type of reserch is descriptive correlational with cross sectional approach. The population of 54 respondent was determined by purposive technique sampling. The instrumen use CES-D. Univariate data were analyzed using frequency distribution and Chi Square for correlation. The results showed that almost all data (62.96â„…) had undergone haemodialysis for 3 years and almost all data (81.48%) had depression symptomps. And there waswas relationship between the duration of undergoing haemodialysis with depression in chronic renal failure patients in Majalaya District Hospitals with pvalue 0.003(<0.05, r = 0.417). For nurse s it is expected to provide nursing care that is not only physical but psychosocial as well, so the depression can be resolved soon